The Fate of a Part-Time Learner: Russian Graduates of Part-Time Higher Education Programmes in the Labour Market - Ksenia V. Rozhkova; Sergey Yu. Roshchin; Pavel V. Travkin (Вопросы образования)
This article examines the career outcomes of Russian university graduates who received higher education in a part-time form. The study is based on comprehensive administrative data on the employment of bachelor’s and specialist’s degree holders who graduated in 2018 and 2022. We apply Heckman-corrected wage regressions and Oaxaca-Blinder decomposition to identify the factors affecting the difference in wages between graduates of full-time and part-time programmes. The findings revealed that 70% of part-time programmes graduates remain in the same position one year after graduation and do not receive any substantial wage increase, in contrast to their full-time counterparts. Furthermore, graduates of full-time programmes earn, on average, 3–5% more than part-time graduates one year after graduation, and the gap reaches 22% in favour of full-time graduates five years after graduation, controlling for demographic, educational, employment characteristics, and self-selection. Longer work experience among part-time students, including their experience of combining study and work, reduces the observed wage gap, whereas traditional indicators of educational quality such as type of university and honours degree increase it. The results demonstrate that there is a significant differentiation in the returns to higher education depending on the characteristics of its quality. Furthermore, this differentiation remains uncompensated by work experience and exacerbates with career progression.